Effectiveness of a multicomponent healthcare intervention on blood pressure and lipids among subjects with poorly controlled type 2 diabetes: Findings from the INTEGRA study - Vlacho, Bogdan; Molló Iniesta, Àngels; Gratacòs, Mònica; Mata-Cases, Manel; Rubinat, Esther; Berenguera, Anna; Cos, Francesc Xavier; Franch-Nadal, Josep; Mauricio, Dídac (Primary care diabetes, 2024)
We aimed to evaluate the impact of a multicomponent healthcare intervention, primarily designed to improve glycemic control, on blood pressure and lipids in individuals with poorly controlled type 2 diabetes mellitus (T2DM) in the Catalonian primary care setting A cluster, non-randomized, controlled pragmatic trial was conducted across 11 primary care centers. The intervention group (N=225) received a comprehensive, patient-centered approach, including a dedicated monographic consultation to address therapeutic inertia. The control group (N=181) mirrored the intervention group but lacked the monographic consultation. Secondary endpoints included lipid and blood pressure control assessed at baseline and after a 12-month follow-up. 245 participants completed the study over 12 months. We found no differences in the reduction of lipid laboratory parameters between the groups at the final visit. However, no significant differences were found between the groups for other lipids or the proportion of participants achieving lipid target values. Likewise, no differences were noted between the groups for blood pressure, its target control, and treatment at the final visit. Various clinical factors such as age, sex, diabetes duration, HbA1c levels, BMI, and macrovascular complications among the participants were associated with achieving lipid and blood pressure targets at the final visit. The pragmatic multicomponent intervention proposed in the INTEGRA study, showed that including a component designed to reduce clinical inertia in the management of glycemia did not demonstrate benefits in improving lipids and blood pressure in patients with poorly controlled T2DM. •Numerous patient- and healthcare system-related barriers contribute to this suboptimal control.•Intervention had no effect on lipid profile target control•Intervention had no effect on blood pressure or blood pressure target control•Age, sex, T2DM duration, HbA1c, BMI, and T2DM complications were associated with targets of lipid and blood pressure